MEKANISME BERTAHAN HIDUP (SURVIVAL MECHANISM) MASYARAKAT BANTARAN SUNGAI RUNGAN KELURAHAN PETUK KATIMPUN - Atem, Atem; Batubara, Muhammad Zusanri; Angela, Vivi Friskila; Santoso, Yonatan Ari; Simbolon, Wahyu; Kurniawan, Rizky (Jurnal Ilmiah Sosiologi Agama (JISA), 2024)
This research aims to examine the livelihoods of Petuk Katimpun Village fishermen facing ecological, economic, and flooding problems. The research method used is qualitative and literature study. Data collection techniques included participant observation, interviews, literature study, and documentation. The results revealed that the river is a living space that cannot be separated to support the various needs and livelihood activities of the Petuk Katimpun community. The availability of natural resources in the river basin is utilized to maintain a sustainable life. Communities living along the banks of the Rungan River tend to have complex problems, especially against disasters and ecological damage to the river environment, which disrupts the community’s livelihood system. The people of Petuk Katimpun use the Rungan River to catch fish, find rattan, and conduct gold mining. In addition, the Rungan River is used to access lakes and swamp forests and catch fish using boats. The survival strategies carried out by Petuk Katimpun fishermen are, first, tying the belt tighter, namely saving money but not reducing the portion and quality of food and saving when the income is significant. Second, job diversification (alternative subsistence) is done by doing various jobs to increase revenue, such as the work done by fishermen, such as looking for rattan. In contrast, the fisherman’s wife becomes a seller of fish caught by her husband. Third, by utilizing social networks such as relatives, acquaintances, or neighbors to gain access to specific resources such as assistance or information on fishing areas, the fishermen’s wives also form arisan groups